Bridging Diagnostics: Evaluating the NG-CARBA-5 Test and PCR Among Carbapenem-Resistant Enterobacterales Isolated from a Multidisciplinary Hospital in Malaysia - Parameswaran, Vityashri; Joseph, Narcisse Mary Sither; Amin Nordin, Syafinaz; Sallehhudin, Norlaila; Ibrahim, Rosni (Malaysian Journal of Medical Sciences, 2026)
Background: Carbapenem-resistant Enterobacterales (CRE) pose a major health threat worldwide because of limited treatment options and high mortality rates. This study investigated the detection of CRE in a multidisciplinary hospital by comparing the multiplex polymerase chain reaction (PCR) with the rapid NG-CARBA-5 assay.Methods: A total of 58 bacterial isolates, previously recovered from various clinical specimens, were tested. Genotypic identification was performed using a multiplex PCR assay targeting carbapenemases, including blaKPC, blaNDM, and blaOXA-48. The rapid assay was conducted using the NG-CARBA-5 test kit to detect blaNDM, blaIMP, blaVIM, blaOXA-48, and blaKPC.Results: Out of the 58 isolates tested, 36 were identified as carbapenemase producers with the rapid assay, whereas 39 were detected by PCR. All 36 carbapenemase-positive isolates detected by the rapid assay harboured the blaNDM gene, while multiplex PCR detected 19 isolates with multigenes (18 blaNDM+blaKPC and 1 blaNDM+blaOXA) and 20 isolates with single genes (18 blaNDM, 1 blaOXA, and 1 blaKPC). Discrepancies were observed among the detection methods, with four isolates reported as false negatives (FNs). This indicates a possible risk of missing colonised or infected patients, which is important in settings such as intensive care units or outbreaks.Conclusion: The NG-CARBA-5 test is suitable for rapid initial screening, particularly when complemented by another phenotypic test such as the modified carbapenem inactivation method (mCIM) test.